2015
DOI: 10.1136/bcr-2015-212839
|View full text |Cite
|
Sign up to set email alerts
|

Under seize: neurocysticercosis in an immigrant woman and review of a growing neglected disease

Abstract: Summary Neurocysticercosis (NCC) is a significantly neglected tropical disease and, with increasing globalisation, a notable emerging infection in the developed world. We describe a case of ventricular NCC in a 22-year-old Mexican-American woman with a history of seizures, who presented with 2 weeks of headaches and intermittent fevers progressing to altered mental status and vomiting. Initial imaging revealed a cystic mass at the posteroinferior aspect of the third ventricle superior to the aqueduct of Sylviu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
7
2
Order By: Relevance
“…Other symptoms mainly were movement disorder, nausea, and vomiting. Most patients presented with epileptic seizures [ 18 , 19 ], but our case did not. A review showed that over 50% of patients with subarachnoid cerebral cysticercosis have imaging evidence of vasculitis [ 20 ].…”
Section: Discussioncontrasting
confidence: 55%
“…Other symptoms mainly were movement disorder, nausea, and vomiting. Most patients presented with epileptic seizures [ 18 , 19 ], but our case did not. A review showed that over 50% of patients with subarachnoid cerebral cysticercosis have imaging evidence of vasculitis [ 20 ].…”
Section: Discussioncontrasting
confidence: 55%
“…Other symptoms mainly were movement disorder, nausea and vomiting. Most patients presented with epileptic seizures [16,17], but our case did not. A review showed over 50% of patients with subarachnoid cerebral cysticercosis have imaging evidence of vasculitis [18].…”
Section: Discussioncontrasting
confidence: 53%
“…(5) In 2010, the World Health Organization (WHO) listed NCC as an unattended zoonosis in permanent expansion, thus turning it into a serious public health issue in developed countries due to migratory phenomena. (3,6) Flórez-Sánchez et al (7) found that the prevalence of seropositivity for cysticercosis varies in the Colombian population (0.53-40.19%) and that the Vaupés department has the highest seroprevalence rates.…”
Section: Introductionmentioning
confidence: 99%